Policy Implementation of Asahan Regent Regulation No. 3 of 2019 Concerning Adjustment of Retribution Rates for Parking Services on Public Roads in the Asahan Regency Area - Hatta Syahputra; Budi Hartono; Dumasari Harahap (Universitas Medan Area, 2023)
This study aims to analyze the Policy Implementation of Asahan Regent Regulation Number 3 of 2019 Concerning Adjustment of Retribution Rates for Parking Services on Public Roadsides in the Asahan Regency Area and the obstacles. This research uses a qualitative descriptive research type, which is a method that describes and explains the results in the field in the form of words between sentences which are then drawn conclusions from the description. Based on the results of interviews and observations in the field which were then analyzed in this study, the results and conclusions of the parking levy policy on public roads in Asahan Regency have not been implemented properly. parking fees that are not in accordance with the provisions of the regulations and people who do not pay according to the rates, then the indicators for collecting fees in this study are still found by parking officers who do not use complete attributes in collecting fees. Then the indicators of supervision and sanctions, the results of the surveillance research conducted by the Department of Transportation are quite good but there are still violations committed by parking attendants.